2005
DOI: 10.1111/j.1445-2197.2005.03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Routine and Selective Operative Cholangiography

Abstract: There was no difference between policies of routine or selective IOC in relation to operating times, retained CBD stone rates or CBD injury. However, the authors found management of patients with recurrent biliary symptoms easier if an IOC had been performed, and IOC was easier to perform when the staff were expecting it. Thus a policy of routine IOC has been adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…9,10 Several studies have evaluated the use of IOC in preventing CBD injury and have concluded that both routine and selective IOC are acceptable policies for reducing the risk of CBD injury. [11][12][13] However, many studies are underpowered and, therefore, offer limited evidence on the efficacy of IOC in reducing the rate of CBD injury. This was addressed in 2002 by a metaanalysis of 40 case-series that included 327,523 laparoscopic cholecystectomies, and calculated that routine use of IOC halved the rate of CBD injury.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several studies have evaluated the use of IOC in preventing CBD injury and have concluded that both routine and selective IOC are acceptable policies for reducing the risk of CBD injury. [11][12][13] However, many studies are underpowered and, therefore, offer limited evidence on the efficacy of IOC in reducing the rate of CBD injury. This was addressed in 2002 by a metaanalysis of 40 case-series that included 327,523 laparoscopic cholecystectomies, and calculated that routine use of IOC halved the rate of CBD injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several image modalities have been proposed for intraoperative visualization of the bile duct system, including routine use of intraoperative X‐ray cholangiography 8, 9, 10. However, opinions are divided on the effectiveness of intraoperative X‐ray cholangiography to avoid bile duct injury 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Routine IOC is further applied if laparoscopic CBD clearance is favored. Secondly, IOC can be used only selectively [41][42][43][44] .…”
Section: Intraoperative Cholangiographymentioning
confidence: 99%